THE SCHOOL'S FUNCTION AND THE INFLUENCE OF CULTURAL CAPITAL ON STUDENTS' PERFORMANCE - Lopes Carmignolli, Andreza Olivieri [UNESP]; Muzzeti, Luci Regina [UNESP]; Celli de Oiveira, Maria Fernanda [UNESP] (Univ Federal Sergipe, 2020)
This is an excerpt of a master's dissertation titled The influence of cultural, social and economic capitals on the students' school trajectory success. It aimed to analyse how cultural capital influences the students' school performance through their family's mores and school experiences, when observing their behaviours regarding musical styles, reading practices and sports activities. The family environment is where people initially acquire cultural capital, being legitimized within a set of socially recognized knowledge and cultural assets. The studies of Pierre Bourdieu through the concepts of habitus, cultural, economic and social capital guided the theoretical reference. We chose the qualitative research method named Bourdieusian praxeology, because it is related to the restructuring of the habitus. The results of the work show how important is the partnership between the school and the family for a successful school performance.
Keywords: School's role; Cultural capital; School performance; Habitus